Effects of autoclaving (Pleurotus osteratus) spent mushroom substrate water extract on the minerals, elicitors, cassava yield, and the management of African cassava mosaic virus - Samuel Okere; Anthony Eromosele Ataga (International Journal of Advances in Applied Sciences, 2021)
Farmers all over the world spend millions of dollars to partially control plant diseases that attack their crops using agrochemicals that pollute the environment. Plant diseases reduce crop yield, quality, and shelf life. Enhancing the inherent ability of plants to resist diseases using elicitors and minerals is one of the neglected, sustainable, low-cost, and environmentally friendly approaches to ensure the continued supply of food and fiber. Therefore the aim of this paper is to evaluate the composition of the elicitors and minerals in autoclaved and unautoclaved water extract of Pleurotus osteratus spent mushroom substrate and the effects of its application on the management of African cassava mosaic virus (ACMV), growth, and yield of cassava. The treatments for this investigation comprised Pleurotus osteratus water extract spent mushroom substrate (POWESMS), Pleurotus osteratus autoclaved spent mushroom substrate (POAWESMS), and untreated cassava plants as control. The mineral compositions and the elicitors in the treatments were evaluated using standard procedures. The data generated were subjected to analysis of variance (ANOVA) at (p=0.05). The results obtained from this investigation revealed significant differences in the values of resistant elicitors and minerals. Significant differences were also recorded for the growth, yield parameters, and disease severity evaluated at 4 weeks intervals. The results showed that unautoclaved water extract performed significantly better than the autoclaved in reducing African cassava mosaic disease (ACMD) severity which did not translate to higher crop yield.